Refleksi Peran Usaha Mikro Dalam Perwujudan Kesejahteraan Ekonomi Berbasis Eco-Micro Enterprise - Yakub, Mardatillah; Siradjuddin, Siradjuddin; Sudirman, Sudirman (Economics and Digital Business Review, 2023)
This study aims to conduct an analysis and study of the role of micro enterprises in the realization of economic welfare based on eco-micro enterprise. The research method used is a normative approach with a method of collecting and analyzing literature data. Based on the discussion that has been described, it can be concluded that although the role of MSMEs has been regulated and affirmed through Law No. 20 of 2008 concerning Micro, Small and Medium Enterprises and Government Regulation No. 7 concerning the Convenience, Protection and Empowerment of Cooperatives and Micro, Small and Medium Enterprises, MSMEs have not been able to carry out their existing roles optimally. There are many factors that make this happen such as community culture, capital, literacy, and so on. The reflection of this imperfection is clearly seen in the various social realities that come to the surface. Then the concept of eco-micro enterprise is presented as a solution to existing problems as well as an affirmation that micro businesses are not only limited to profit (profit) and people (customers) but also plants (environment). Therefore, concern for micro businesses from various parties is expected so that these micro businesses can carry out the role entrusted to the maximum.